Trabecular microbypass stent implantation in pseudophakic eyes with open‐angle glaucoma: Long‐term results. Issue 4 (April 2019) - Ferguson, Tanner J.; Ibach, Mitch; Schweitzer, Justin; Karpuk, Kayla; Stephens, David J.; Sudhagoni, Ramu; Berdahl, John P.
Abstract : Purpose : To evaluate the long‐term safety and efficacy of a trabecular microbypass stent as a sole procedure in pseudophakic eyes with open‐angle glaucoma. Setting : Private practice; Sioux Falls, South Dakota, USA. Design : Retrospective, consecutive case series. Methods : The series included pseudophakic eyes of patients with mild to severe open‐angle glaucoma (OAG) implanted with 1 trabecular microbypass stent. Data was collected at baseline before the surgery and at 1 day, 1 week, 1 month, and up to 48 months postoperatively. The data included intraocular pressure (IOP), number of glaucoma medications, and whether there was a requirement for secondary surgery. Results : The study comprised 40 patients (51 eyes). The mean IOP was reduced from 20.33 mm Hg ± 4.83 (SD) at baseline to 15.65 ± 3.45 mm Hg at 48 months postoperatively, indicating a 23% reduction ( P < .01). The mean number of glaucoma medications was 2.08 ± 1.06 preoperatively and 1.46 ± 1.07 at 48 months postoperatively ( P > .05). Postoperatively, 3 eyes (6%) had IOP spikes of 15 mm Hg or higher than the preoperative value, which responded to topical therapy. Ten eyes (20%) required secondary glaucoma surgery. There were no postoperative or intraoperative complications. Patients who had previous ocular hypotensive medication use and an IOP of 18 mm Hg or higher achieved a statistically significant reduction in both IOP and medication use. Conclusions : The insertion of a single trabecular microbypass stent effectively provided a sustained reduction in IOP in pseudophakic patients with mild to severe OAG. The IOP reduction was more robust in eyes that had a higher baseline IOP.